Capital Structure, Liquidity, Profit Growth, and Financial Performance of Culinary MSMEs Using Local Raw Materials - Pirdaus, Dede Irman; Suhaimi, Nurnisaa binti Abdullah; Sidiq, Fahmi (Rescollacom (Research Collaborations Community), 2024)
This study examines the capital structure, liquidity, profit growth, and financial performance of micro, small, and medium-sized enterprises (MSMEs) in the culinary sector based on local raw materials in Tasikmalaya City. A quantitative research approach with a descriptive-analytical method was employed, analyzing data from 33 sampled MSMEs. The findings reveal that the majority of MSMEs maintain a satisfactory capital structure, adequate liquidity, and positive profit growth. Furthermore, the financial performance of these MSMEs, particularly in terms of profitability, is commendable. The study concludes that there is a positive relationship between capital structure, liquidity, profit growth, and financial performance in these MSMEs, highlighting the importance of effective management in achieving business success.